Competing for academic labor: Research and recruitment outside the academic center - ORTIGA, Yasmin Y. (Institutional Knowledge at Singapore Management University, 2020)
Increasing competition among research universities has spurred a race to recruit academic labor to staff research teams, graduate programs, and laboratories. Yet, often ignored is how such efforts entail negotiating a pervasive hierarchy of universities, where elite institutions in the West continue to attract the best students and researchers across the world. Based on qualitative interviews with 59 Singapore-based faculty, this paper demonstrates how migrant academics in competitive universities outside the West take on the burden of seeking other ways of attracting academic labor into their institutions, often resorting to ethnic and transnational ties to circumvent limits imposed by a hierarchical higher education landscape. Those unable to utilize these transnational strategies are less likely to maintain the pace of productivity expected by their institutions, heightening anxieties regarding tenure and promotion. In examining the Singapore case, this paper reveals the disjunctures between the increasing pressures of growing universities eager to compete in a global higher education system, and the everyday realities of academic production within these institutions.